This I Believe - Cantrell, Hadley (Tufts Archival Research Center, 2006)
Hadley Cantrell describes the differences between knowledge, beliefs, and emotions, and states his belief that human beings are essentially the same in their needs and aspirations, and that satisfaction comes through high quality work motivated by love.